2019
DOI: 10.1038/s41598-018-38441-2
|View full text |Cite
|
Sign up to set email alerts
|

Elastic net-based prediction of IFN-β treatment response of patients with multiple sclerosis using time series microarray gene expression profiles

Abstract: INF-β has been widely used to treat patients with multiple sclerosis (MS) in relapse. Accurate prediction of treatment response is important for effective personalization of treatment. Microarray data have been frequently used to discover new genes and to predict treatment responses. However, conventional analytical methods suffer from three difficulties: high-dimensionality of datasets; high degree of multi-collinearity; and achieving gene identification in time-course data. The use of Elastic net, a sparse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…One study used a feature selection computational method on a longitudinal microarray dataset of relapse-remitting MS (RRMS) patients treated with IFNb-1b, and found a predictive seven gene signature (CXCL9, IL2RA, CXCR3, AKT1, CSF2, IL2RB, GCA) with 65.08% predictive accuracy (59). Using an alternative method of Elastic net modeling, Fukushima et al analyzed time-course microarray datasets from PBMCs of MS patients and identified eleven (ZBTB16, ZFP37, HPS5, HOPX, ARFGAP3, CALML5, VPS26A, SLC5A4, MBL2, DLGAP4, CACNA1C) and eight (SMA4, MIR7114_NSMF, LSM8, FLAD1, RRN3P1, RASL10A, IER3IP1, CDH2) genes predictive of an IFNb response, with 81% and 78% accuracy, respectively, for each dataset (60). A different study employed the GeneRank method to identify monotonically expressed genes (MEGs) that determine a good response (AFTPH, ALOX5, ATG7, MYD88, LILRB1, PRKAB1, PSEN1, VAMP3) and a bad response (AGFG1, CHM, IGLL1, PELI1, PTEN) for responders, and two bad response MEGs for non-responders (NAP1L4, MMS19) in IFNb treated RRMS patients (61).…”
Section: Canonical and Non-canonical Signaling In Autoimmune Diseasesmentioning
confidence: 99%
“…One study used a feature selection computational method on a longitudinal microarray dataset of relapse-remitting MS (RRMS) patients treated with IFNb-1b, and found a predictive seven gene signature (CXCL9, IL2RA, CXCR3, AKT1, CSF2, IL2RB, GCA) with 65.08% predictive accuracy (59). Using an alternative method of Elastic net modeling, Fukushima et al analyzed time-course microarray datasets from PBMCs of MS patients and identified eleven (ZBTB16, ZFP37, HPS5, HOPX, ARFGAP3, CALML5, VPS26A, SLC5A4, MBL2, DLGAP4, CACNA1C) and eight (SMA4, MIR7114_NSMF, LSM8, FLAD1, RRN3P1, RASL10A, IER3IP1, CDH2) genes predictive of an IFNb response, with 81% and 78% accuracy, respectively, for each dataset (60). A different study employed the GeneRank method to identify monotonically expressed genes (MEGs) that determine a good response (AFTPH, ALOX5, ATG7, MYD88, LILRB1, PRKAB1, PSEN1, VAMP3) and a bad response (AGFG1, CHM, IGLL1, PELI1, PTEN) for responders, and two bad response MEGs for non-responders (NAP1L4, MMS19) in IFNb treated RRMS patients (61).…”
Section: Canonical and Non-canonical Signaling In Autoimmune Diseasesmentioning
confidence: 99%
“…We examine the predictive ability on the prediction of binary drug response and ordinal EDSS response. For the binary case, we apply a number of classifiers including two linear models (EN-LR 8 and SVM), one nonlinear model ( K -nearest neighbors (KNN) 30 ), and a probabilistic graphical model (discriminative loop hidden Markov model (dl-HMM) 14 ) to real-world time-course data. We did not include SVM with nonlinear kernels (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…In parallel with these technological developments, there has been growing interest in the application of machine learning methods to analyze the time-course gene expression data. For example, time-course gene expression data can be used to not only identify longitudinal phenotypic markers 11 , 12 , but also assess the association between the time course molecular data and cytokine production in this HIV trial 13 and predict drug response during a treatment 8 , 14 . In 15 , the authors proposed an integrated Bayesian inference system to select genes for drug response classification from time-course gene expression data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the therapeutic mechanism of IFN-β has not been fully elucidated, microarray experiments have been used to evaluate long-term response to IFN-β treatment. However, the resulting longitudinal gene expression profiles have usually been analyzed using statistical methods incapable of dealing with such data [5]. e inconsistency between the data and the analysis methods may cause biased or even totally incorrect conclusions, making it difficult to unravel the mechanism of action of IFN-β in MS. erefore, a reanalysis of longitudinal gene expression data using a machine learning method capable of identifying genes that present a consistently changed pattern across time is recommended.…”
Section: Introductionmentioning
confidence: 99%